UJI KESADAHAN AIR TANAH DI DAERAH SEKITAR PANTAI KECAMATAN REMBANG PROPINSI JAWA TENGAH - Sulistyani .; Sunarto .; Annisa Filaeli (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2012)
Research on soil water hardness,calcium and magnesium covers have been done. Samples were analyzed groundwater in the area around Rembang Coast District Central Java Province. Samples taken from four villages located around the coast and every village three samples taken at random. Samples of water was added HNO3(c), plus the ionization buffer solution, and analyzed using Atomic Absorption Spectrophotometer. Sample concentration is determined using a calibration curve. From the research results can be concluded that the hardness of water wells in the District Rembang remained at normal concentrations far below the dangerous threshold, ie below 200 ppm. Thus, in terms of water hardness district wells in the area especially along the coast of Rembang District is safe to use for everyday purposes and industrial use of fish. From the results of the analysis is also known that the dominant of hardness of water wells in the area is soft water so that the level of hardness can be reduced significantly by means of heating, which can be reduced by 90%.